NARATOR DAN KEBERULANGAN CERITA DALAM FILM PERFUME THE STORY OF A MURDERER - Agung Sutrisno (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research article has to describe the role of the narrator and the repetition that occurs in the film "Perfume The Story of A Murderer". Material objects in this research article is the film "Perfume The Story of A Murderer". Formal objects in this research article is the location of the narrator and the frequency contained in film "Perfume The Story of A Murderer", with narratology theory from Gerard Ganette. The methods used in this research article is descriptive qualitative with a structural approach. The results obtained in this research article indicate that the narrator has a function to direct the audience to understand the story visually presented in the film, and the film "Perfume The Story of A Murderer" raises a recurrence in the telling as the main values in the film's story.Key word: Narrator, Repetition, Naratology, Film